The impact of Sudafed on spleen of albino mice - L. Alsaadi Yasmin; K. Abdul Ameer Bassam; Jasim Mohamad Ban; Kathum Omra Faiza (Medičnì Perspektivi)
Pseudoephedrine (PSE), often known as Sudafed, belongs to a class of medications known as sympathomimetic amines, which affect the digestive system, respiratory system, and cardiovascular system. This drug has a long history of medical use; it is helpful in treating symptoms of the common cold and flu, sinusitis, asthma, and bronchitis. Due to its central nervous system (CNS) stimulant properties and structural similarity to amphetamine, it is also used for non-medical purposes such as doping agent, to increase focus, and as a substance that gets rid of exhaustion and drowsiness. Nevertheless only a few studies, backed up its impact on solid abdominal organs. The aim of this task is to investigate the effect of some dosages of PSE medication on the histology of albino mice's spleens. The current study included 18 albino mice grouped into 2 groups: control (3 mice), and acute group (15 mice). The acute group was further divided into five subcategories with 3 mice in each, and the animals received a single intraperitoneal injection of 0.3 ml of each of the following concentrations of drug for 24 hours: 500 mg/kg, 250 mg/kg, 125 mg/kg, 62.52 mg/kg, and 31.24 mg/kg. After the mentioned period, the mice of all subgroups were sacrificed and the spleens were removed, processed, sectioned and stained for histological analysis. Results showed that the amount of PSE administered at 500 mg/kg caused considerable sago spleen, numerous amyloid depositions in peripheral zone, sinusoidal red pulp congestion, and hyperplasia inside the germinal center. While less powerful effects or no detectable pathological alterations were seen at lower doses (125, 62.52, and 31.24 mg/Kg). This investigation demonstrated some pathological effects of this drug on spleen of albino mice at higher doses as compared to lower doses and control which recommends the use of minimal doses of PSE to avoid its adverse effects.